Discourse and dialogue = Diskurs und Dialog - Pon, Leonard (Peter Lang, 2012)
The volume consists of 20 original papers by linguists from different European universities on the subject of dialogue forms in selected discourse areas. The broad title Discourse and Dialogue takes into account the heterogeneity of approaches typical of modern European discourse research, which is also reflected in this volume.